Development of ELISAs for the detection of interferon-gamma in rhinoceroses and elephants as diagnostic tools for Mycobacterium bovis and Mycobacterium tuberculosis infections - Godfroid, Jacques (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.